2013
DOI: 10.5216/ree.v15i3.18631
|View full text |Cite
|
Sign up to set email alerts
|

Necessidades humanas básicas e dependência de cuidados de enfermagem de idosos institucionalizados

Abstract: Necessidades humanas básicas e dependência de cuidados de enfermagem de idosos institucionalizados Basic human needs and nursing care dependency of institutionalized eldersNecesidades humanas básicas y dependencia de cuidados de enfermería en ancianos institucionalizados

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
1
4
0
2
Order By: Relevance
“…As in other studies (26) , the results showed that a large number of requests are to carry out activities related to hygiene and comfort, especially bathing. The elderly have diminished physiological reserve, making them vulnerable to situations of functional dependence, which can last beyond hospital discharge.…”
Section: Discussionsupporting
confidence: 78%
“…As in other studies (26) , the results showed that a large number of requests are to carry out activities related to hygiene and comfort, especially bathing. The elderly have diminished physiological reserve, making them vulnerable to situations of functional dependence, which can last beyond hospital discharge.…”
Section: Discussionsupporting
confidence: 78%
“…Even though full recovery of mobility is not possible in all cases, collaborative interdisciplinary work is required so that impaired mobility does not develop into further incapacities. ( 22 )…”
Section: Discussionmentioning
confidence: 99%
“…Apesar de a total recuperação da mobilidade não ser possível em todos os casos, um trabalho interdisciplinar colaborativo é necessário, assim a mobilidade prejudicada não evolui para outras incapacidades. ( 22 )…”
Section: Discussionunclassified
“…Among other problems, were identified musculoskeletal pain, joint stiffness, unstable gait, and history of falls in the studied elderly, which demonstrates demands of nursing care for their control and reduction. A study conducted in Alagoas/Brazil with institutionalized elderly people identified that in 62.7% of participants, the need for locomotion was affected and they depended on nursing care for the encouragement and supervision of walking, on the use of artifacts for ambulation (orthoses, prostheses, crutches, walking sticks, wheelchairs, walkers) and on effective assistance for locomotion due to restriction to bed, in addition to guidance and supervision of the companion/caregiver (13) .…”
Section: Discussionmentioning
confidence: 99%